IMPLEMENTASI PEMBELAJARAN KONSTRUKTIF UNTUK MENINGKATKAN KEMANDIRIAN DAN PRESTASI MAHASISWA PADA MATA KULIAH MATEMATIKA EKONOMI - Andian Ari Istiningrum (Jurnal Pendidikan Akuntansi Indonesia, 2008)
The aims of this research is to desribe the implementation of constructive learning in Mathematics for Economic course and to gain knowledge about the result of this learning in improving students’ independence and performance. This is a class action research. The Subject of this research is all students following Mathematics for Economics course in Accounting Study Program. The total number of this subject is 49 people. To collect data, researcher uses observation, interviews, questionnaires, assignment and examination, and daily note. The data is analyzed by descriptive analysis. Based on data analysis, the percentation of students who are less independence before they study in class has been 47,17 %. It increases to 44,09 % in first cycle and 41,36 % in second cycle. However, there is an increase in the level of students’ independence because the percentage of students including in the level of less indepence and not indepence decreases significantly and those including in the level of indepence and very independence rises regularly. Therefore, it can be concluded that constructive learning can improve the students’ independence in studying mathematics for economics. It also can be shown in the result of students’ performance. Students’ performance measured by assignments and examinations also increases significantly since there isa tendency that more indepence may result in more performance.